Rezerwat jodłowy „Tisovik” w parku narodowym „Belavežskaja Pušča” na Białorusi - Korczyk, Adolf (Leśne Prace Badawcze, 2016)
Silver firs ( Abies alba Mill.) of natural origin occurring in the Belorussian part of the Białowieża Primeval Forest constitute an enclave situated 120 km to the north-east of a dense fir stand in the Polish part of the forest. In order to protect this population a reserve called „Tisovik” was established. In this study, plant communities occurring in the „Tisovik” reserve were described and its fir population (20 trees) was characterized in terms of its genetic structure.